Performance Improvements of Bixin and Metal-Bixin Complexes Sensitized Solar Cells by 1-Methyl-3-propylimidazolium Iodide in Electrolyte System - Winda Rahmalia; Septiani Septiani; Uray Amira Naselia; Thamrin Usman; Imelda Hotmarisi Silalahi; Zéphirin Mouloungui (Indonesian Journal of Chemistry, 2021)
Bixin is one of the potential natural sensitizers used in dye-sensitized solar cells (DSSCs). In this study, bixin was complexed with Cu(II) and Zn(II) to increase its stability. The formation of the complexes was indicated by shifting peaks absorption and the changes in the fine spectral structure observed from the UV-Vis absorption spectra. The metal-bixin complex occurs due to the interaction between the ester groups of bixin and the metal. Bixin, Cu-bixin, and Zn-bixin were used separately as sensitizers in DSSCs. The DSSCs performance was then improved by adding 1-methyl-3-propylimidazolium iodide (MPII) to the electrolyte system. The presence of MPII 0.4 M in KI-I2 electrolyte produced a higher ionic conductivity value (20.44 mS cm–1) than that without MPII (11.14 mS cm–1). This electrolyte system significantly improved DSSCs performance. Under a light intensity of 300 W/m2, the maximum energy conversion efficiencies of DSSC with bixin, Cu-bixin, and Zn-bixin as sensitizers are 0.084, 0.081, and 0.005%, respectively. The Zn-bixin-based DSSC was stable under high light intensity. Under 700 W/m2, its maximum energy conversion efficiency reaches 0.125%. There was a synergistic work observed between the metal-bixin complex and the MPII based electrolyte. This result can open the way for constructing functional materials for solar cell applications.